Sensitive recovery of recombinant antibody clones after their in silico identification within NGS datasets - Spiliotopoulos, Anastasios; Owen, Jonathan P.; Maddison, Ben C.; Dreveny, Ingrid; Rees, Helen C.; Gough, Kevin C. (Elsevier, 2015)
Recently the analytical power of the latest high throughput next generation DNA sequencing platforms has been used to analyse phage that have been selected from the panning of large combinatorial libraries displaying either peptide or antibody ligands. This process, commonly referred to as next generation phage display (NGPD), allows the researcher to determine the identity of specific phage that are being enriched against an antigen target by analysis of the DNA sequence encoding the displayed ligand. This method bypasses several steps in conventional phage panning that include laborious colony picking and functional ligand screening. A downside of this approach is that the only output from such experiments is the DNA sequence information of such enriched phage particles. In the case of peptides, the peptide sequence can be synthesised directly and used for further screening; however this is more difficult with larger antibody fragments such as ScFvs. In the case of ScFvs, their coding sequence would have to be fully elucidated, synthesised and re-cloned before expression. We describe here the application of an inverse PCR-ligation methodology that enables the specific recovery of ScFvs of interest from enriched sub-libraries of phage clones. Phagemid particles are recovered using sequence information derived from their unique heavy chain CDR3/FR4 domains and specific clones can be recovered irrespective of CDR3 size and at levels of abundance that would be refractory to their discovery during conventional phage panning and screening.